Writing and scientific publication skills of university teachers: A survey study - Derling Jose Mendoza Velazco; Elizeth Mayrene Flores Hinostroza; Josselyn Leonela Muñoz Briones; María Leonila García Cedeño (Journal of Education and Learning (EduLearn), 2023)
In the academic world, the skills of scientific writing and publishing allow for the sharing and dissemination of academic research. The research analysed the scientific publications of university teachers from the Faculty of Humanities and Social Sciences of the Technical University of Manabí (FCHS-UTM), Ecuador, in order to determine their skills and preferences in terms of scientific journals, writing language, type of publication, indexing, and editorial quality. A descriptive quantitative approach study was applied. A survey study was carried out. The sample selection was non-probabilistic and participatory. The sample consisted of 55 teachers from the faculty. A 25-item questionnaire was developed for data collection. The results were analysed using descriptive statistics. Among the results the faculty has a preference for national or local scientific journals. The language most used in studies is Spanish. University researchers are more professional in their use of American Psychological Association (APA) norms. The study presented implications such as the promotion of scientific publication and professional development, preservation of language and culture, professionalism in citation standards, promotion of collaboration, improvement of editorial quality and training strategies.